POLITENESS STRATEGIES IN TIKTOK COMMENTS: A SOCIOPRAGMATIC STUDY - Agnes Ernawati Agnes; joko wibowo (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This research examines the use of politeness strategies in the comment sections of English-learning videos on TikTok from a sociopragmatic perspective. The objectives are to identify the politeness strategies employed by users and to explain how these strategies are realized in English-learning interactions. A descriptive qualitative method with a sociopragmatic approach was adopted. The dataset comprised 124 comments obtained through purposive sampling from five English-learning TikTok videos created by different content creators. The analysis was conducted using Brown and Levinson's theory of politeness strategies. The results indicate that all four politeness strategies were present in the data: Negative Politeness (39.52%), Positive Politeness (33.87%), Off Record (20.97%), and Bald on Record (5.65%). Negative Politeness emerged as the dominant strategy, suggesting that viewers generally conveyed questions, requests, and learning needs in a respectful manner. Furthermore, the findings highlight that the use of politeness strategies contributes to constructive communication, promotes active learner engagement, and strengthens interaction between viewers and content creators. From a sociopragmatic standpoint, the realization of these strategies is closely associated with the educational setting, speakers' communicative intentions, and the social relationships established within English-learning interactions on TikTok.